2019
DOI: 10.26529/cepsj.564
|View full text |Cite
|
Sign up to set email alerts
|

Research-Based Learning in Initial Teacher Education in Catalonia

Abstract: The teaching profession is undergoing significant changes, some of which are imposed by the new paradigm of education. This new context marks the shift from the teachers’ position as ‘knowledge users’ towards the more complex position of ‘knowledge creators’. In this new professional culture adapted to a changing society, teaching as a profession is understood as undergoing a continuous transformation and innovation process, while the professionals in the educational field appear to be research users and resea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…If educational research becomes relevant in the curriculum, students are more likely to use it and know its benefits. These findings are consistent with work by authors such as Demircioglu (2008), Anwaruddin and Pervin (2015), Perines and Murillo (2017), and Agud and Ion (2019). Indeed, this latter research mentions the importance of the decisions made by the faculties involved in teacher training.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If educational research becomes relevant in the curriculum, students are more likely to use it and know its benefits. These findings are consistent with work by authors such as Demircioglu (2008), Anwaruddin and Pervin (2015), Perines and Murillo (2017), and Agud and Ion (2019). Indeed, this latter research mentions the importance of the decisions made by the faculties involved in teacher training.…”
Section: Discussionsupporting
confidence: 92%
“…Studying curriculum design is a complex but necessary task (Young, 2014). Student participation in research and other related activities depends not only on personal factors, such as motivation and initiative, but also on structural ones, such as curriculum design and the strategic actions taken by university faculties (Agud & Ion, 2019).…”
Section: Relevance Of the Curriculum And Of The Professionals Responsmentioning
confidence: 99%
“…The results of the study could also provide empirical evidence to support the benefits of research-based learning in teacher education. It joined other studies that also found an improvement in the quality of teacher development widely (e.g., Agud & Ion, 2019;Alvunger & Wahlström, 2018;Brew & Saunders, 2020;Toom et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
“…Likewise, studies (e.g., Agud & Ion, 2019;Alvunger & Wahlström, 2018;Brew & Saunders, 2020;Toom et al, 2010) have also been conducted on research-based learning (RBL) as an approach to improving the quality of teacher education. The results of previous studies illustrate how RBL develops students' teachers' profession.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation